(untitled) (Bioagro, 2022)
Sugar beet (Beta vulgaris L.) is one of the most cultivated vegetables in Brazil, where water limitation is the main cause of yield loss. This limitation can be attenuated with the application of organic solutes, such as ascorbic acid (AA). The objective was to evaluate the response of sugar beet plants under the application of AA via irrigation water as a strategy to attenuate water deficit. The experiment was carried out at the Centro de Ciências Agrárias of the Universidade Federal da Paraíba, Areia, Brazil, using a randomized complete block design with nine combinations of irrigation depths based on five evapotranspiration percentages (40.0, 51.6, 80.0, 108.4 and 120 % ET) and five doses of AA (0, 0.29, 1.0, 1.71 and 2.0 mM), with three replications, generated from a central composite matrix. Water use efficiency (WUE) and chlorophyll fluorescence index were evaluated. Data were submitted to analysis of variance and, when significant, to a regression analysis. Irrigation depths influenced chlorophyll a, b and total, maximum fluorescence, instantaneous WUE and intrinsic WUE, but no effect was observed for AA. The beet cultivar Maravilha Top Tall Early Wonder exhibits certain physiological mechanisms of tolerance to water stress. The ascorbic acid, in the concentrations and application method used in the study, had no effect on the beet plant response.